What do stakeholders expect from patient engagement: Are these expectations being met?. (1st June 2018) - Boudes, Mathieu; Robinson, Paul; Bertelsen, Neil; Brooke, Nicholas; Hoos, Anton; Boutin, Marc; Geissler, Jan; Sargeant, Ify
Abstract: Background: Meaningful patient engagement (PE) in medicines development and during the life cycle of a product requires all stakeholders have a clear understanding of respective expectations. Objective: A qualitative survey was undertaken to understand stakeholder expectations. Design: The survey explored 4 themes from the perspective of each stakeholder group: meaning, views, expectations and priorities for PE. Participants were grouped into 7 categories: policymakers/regulators; health‐care professionals (HCPs); research funders; payers/purchasers/HTA; patients/patient representatives; pharmaceutical/life sciences industry; and academic researchers. Results: Fifty‐nine interviews were conducted across a range of geographies, PE experience and job seniority/role. There was consensus across stakeholders on meaning of PE; importance of promoting PE to a higher level than currently; need for a more structured process and guidance. There was little consensus on stakeholder expectations and roles. Policymakers/regulators were expected by others to drive PE, create a framework and facilitate PE, provide guidelines of good practice and connect stakeholders, but this expectation was not shared by the policymakers/regulators group. HCPs were seen as the link between patients and other stakeholders, but HCPs did not necessarily share this view. Discussion and conclusions: Despite broad stakeholder categories, clear themes emerged: there is no "leader"; no stakeholder has a clear view on how to meaningfully engage with patients; there are educational gaps; and a structure and guidance for PE is urgently required. Given the diversity of stakeholders, there needs to be multistakeholder collaborative leadership. Effective collaboration requires consensus on roles, responsibilities and expectations to synergize efforts to deliver meaningful PE in medicines life cycle.